MODEL KOMUNIKASI ANTARETNIK DI PERBATASAN (Studi kasus Etnik Iban dan Melayu di Badau) - Ibrahim Ibrahim (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
In recent decades, the issue of ethnicity is an issue of lively chatter, especially regarding issues of social relations and conflicts often occur in many areas of the country, not least in West Kalimantan. In the interior of Kapuas Hulu, precisely in Badau, a form of ethnic communities can coexist in peace and harmony, namely ethnic Iban and Malays. Social history shows that there has been significant conflict between the two ethnics. It seemed to be an exception to some cases of ethnic conflict in the social history in West Kalimantan. Field research is found several factors that the reason for the establishment of good communication and harmonious inter-ethnic Iban and Malays in Badau. In the political aspect showed as shape of togetherness and good political cooperation in the form of